Multivariate TVaR-based risk decomposition for vector-valued portfolios - Mélina Mailhot; Mhamed Mesfioui (Risks, 2016)
In order to protect stakeholders of insurance companies and financial institutions against adverse outcomes of risky businesses, regulators and senior management use capital allocation techniques. For enterprise-wide risk management, it has become important to calculate the contribution of each risk within a portfolio. For that purpose, bivariate lower and upper orthant tail value-at-risk can be used for capital allocation. In this paper, we present multivariate value-at-risk and tail-value-at-risk for d>2, and we focus on three different methods to calculate optimal values for the contribution of each risk within the sums of random vectors to the overall portfolio, which could particularly apply to insurance and financial portfolios.
Keywords: 330; multivariate tail value-at-risk; risk contribution; capital allocation; risk decomposition